English as a foreign language-teachers' perspectives on implementing online instruction in the Iranian EFL context - Reza Dashtestani (Association for Learning Technology, 2014)
This study set out to explore Iranian English as a foreign language (EFL) teachers' perceptions on the implementation of online EFL instruction. A mixed-methods design, including semi-structured interviews and questionnaires, was employed for the specific purposes of this study. A total of 242 EFL teachers participated in the questionnaire phase of the study. In addition, 46 EFL teachers participated in the interview phase of the study. The teachers worked at a number of universities, schools and language-teaching institutions in Iran. Results suggest that although the Iranian EFL teachers adopted moderately positive attitudes towards the implementation of online instruction, the majority of them preferred blended instruction to online instruction. At the same time, the study revealed that the implementation of online EFL instruction in Iran is challenging due to a number of perceived impediments and obstacles. The most considerable perceived challenges to the implementation of online EFL instruction comprise lack of online facilities and resources, lack of interaction in online instruction, cultural resistances to online instruction and teachers' limited knowledge of online instruction. The findings of this study provided crucial insights into teachers' perspectives on a number of measures that can be adopted to facilitate the integration of online instruction in the EFL context of Iran. The findings would provide valuable insights for educational authorities and course designers to integrate online instruction into the EFL curriculum.